Going GAS : from VBA to Google Apps Script - Mcpherson, Bruce (Computer programmer) (O'Reilly, 2016)
Whether you're moving from Microsoft Office to Google Docs or simply want to learn how to automate Docs with Google Apps Script, this practical guide shows you by example how to work with each of the major Apps Script services. Office still supports VBA, but it's not likely to do so for much longer. If you're a VBA or .NET developer, you'll learn how to port existing VBA code and structure to their JavaScript-based Apps Script equivalents with minimal effort. Author Bruce Mcpherson introduces JavaScript basics for experienced developers unfamiliar with the language, and demonstrates ways to.